DESIGN OF CASH SALES ACCOUNTING INFORMATION SYSTEM USING RESOURCE EVENT AGENT MODEL AS TOOL IN EDDY MOTOR OFFICIAL WORKSHOP - Ardiprawiro (International Journal Management and Economic, 2023)
The role of information systems for accounting is very large because it changes from manual recording to computerized records, so the need for a good database design is essential. A database that meets the normalization rules is needed to support a computerized Accounting Information System (AIS). The Entity Relationship Model (E-R Model) is commonly used to design databases. However, drawing diagrams’ rules are unclear, making it difficult for the data designer to form a database that meets the normalization rules. The REA model is a development of the E-R Model. The REA model was first conceptualized as a framework for building accounting systems in a shared data environment both within companies and between companies. The core feature of the REA model is an object pattern consisting of two mirror images representing the semantics of a business process's input and output components (give-to-get), making it easier to build a data model.